The Pan social brain: An evolutionary history of neurochemical receptor genes and their potential impact on sociocognitive differences. Issue 152 (March 2021) - Staes, Nicky; Guevara, Elaine E.; Helsen, Philippe; Eens, Marcel; Stevens, Jeroen M.G.
Abstract: Humans have unique cognitive capacities that, compared with apes, are not only simply expressed as a higher level of general intelligence, but also as a quantitative difference in sociocognitive skills. Humans' closest living relatives, bonobos ( Pan paniscus ), and chimpanzees ( Pan troglodytes ), show key between-species differences in social cognition despite their close phylogenetic relatedness, with bonobos arguably showing greater similarities to humans. To better understand the evolution of these traits, we investigate the neurochemical mechanisms underlying sociocognitive skills by focusing on variation in genes encoding proteins with well-documented roles in mammalian social cognition: the receptors for vasopressin ( AVPR1A ), oxytocin ( OXTR ), serotonin ( HTR1A ), and dopamine ( DRD2 ). Although these genes have been well studied in humans, little is known about variation in these genes that may underlie differences in social behavior and cognition in apes. We comparatively analyzed sequence data for 33 bonobos and 57 chimpanzees, together with orthologous sequence data for other apes. In all four genes, we describe genetic variants that alter the amino acid sequence of the respective receptors, raising the possibility that ligand binding or signal transduction may be impacted. Overall, bonobos show 57% more fixed substitutions than chimpanzees compared with the ancestral Pan lineage. Chimpanzees, show 31% more polymorphic coding variation, in line with their larger historical effective population size estimates and current wider distribution. An extensive literature review comparing allelic changes in Pan with known human behavioral variants revealed evidence of homologous evolution in bonobos and humans ( OXTR rs4686301(T) and rs237897(A)), while humans and chimpanzees shared OXTR rs2228485(A), DRD2 rs6277(A), and DRD2 rs11214613(A) to the exclusion of bonobos. Our results offer the first in-depth comparison of neurochemical receptor gene variation in Pan and put forward new variants for future behavior–genotype association studies in apes, which can increase our understanding of the evolution of social cognition in modern humans.